SiASR4, the Target Gene of SiARDP from Setaria italica, Improves Abiotic Stress Adaption in Plants - Li, Jianrui; Dong, Yang; Li, Cong; Pan, Yanlin; Yu, Jingjuan (Frontiers in Plant Science, 2017)
Drought and other types of abiotic stresses negatively affect plant growth and crop yields. The abscisic acid-, stress-, and ripening-induced (ASR) proteins play important roles in the protection of plants against abiotic stress. However, the regulatory pathway of the gene encoding this protein remains to be elucidated. In this study, the foxtail millet (Setaria italica) ASR gene, SiASR4, was cloned and characterized. SiASR4 localized to the cell nucleus, cytoplasm and cytomembrane, and the protein contained 102 amino acids, including an ABA/WDS (abscisic acid/water-deficit stress) domain, with a molecular mass of 11.5 kDa. The abundance of SiASR4 transcripts increased after treatment with ABA, NaCl and PEG in foxtail millet seedlings. It has been reported that the Setaria italica ABA-responsive DRE-binding protein (SiARDP) binds to a DNA sequence with a CCGAC core and that there are five dehydration-responsive element (DRE) motifs within the SiASR4 promoter. Our analyses demonstrated that the SiARDP protein could bind to the SiASR4 promoter in vitro and in vivo. The expression of SiASR4 increased in SiARDP-overexpressing plants. SiASR4-transgenic Arabidopsis and SiASR4-overexpressing foxtail millet exhibited enhanced tolerance to drought and salt stress. Furthermore, the transcription of stress-responsive and reactive oxygen species (ROS) scavenger-associated genes was activated in SiASR4 transgenic plants. Together, these findings show that SiASR4 functions in the adaption to drought and salt stress and is regulated by SiARDP via an ABA-dependent pathway.